Prevalence and predicting factors of alcohol use among school going adolescents in a hilly state of Northern India - Durgesh Kumari; Anmol Gupta; Anita Thakur (Wolters Kluwer Medknow Publications, 2022)
Background: Alcohol use among adolescents is rising globally. This habit starts in adolescence and continues throughout their life. Alcohol addiction is associated with many other risky behaviors. Social environmental interventions will be an effective measure to control the problem of alcohol use. Objectives: The purpose of this study was to estimate the prevalence of alcohol use among adolescents and to investigate the associated risk and protective factors. Methods: A cross-sectional study was carried out among school going adolescents in the hilly state Himachal. A pre-validated, self-administered questionnaire was used for data collection. Results: The prevalence of alcohol use in adolescent was 6.1% (10.7% in males and 0.4% in females). Binary logistic regression model revealed that parent's and peer's drinking behavior significantly predicts an adolescent's drinking behavior. Conclusion: Our research supports the need for an adolescent health program involving school, peers, and family. Life skill education should be given to the adolescents to inculcate the resilience so that they learn to say no to peers who try to pull them into such habits.